2020
DOI: 10.1017/s0142716420000582
|View full text |Cite
|
Sign up to set email alerts
|

Limits on expectation-based processing: Use of grammatical aspect for co-reference in L2

Abstract: This study examines the use of discourse-level information to create expectations about reference in real-time processing, testing whether patterns previously observed among native speakers of English generalize to nonnative speakers. Findings from a visual-world eye-tracking experiment show that native (L1; N = 53) but not nonnative (L2; N = 52) listeners’ proactive coreference expectations are modulated by grammatical aspect in transfer-of-possession events. Results from an offline judgment task show these L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 60 publications
1
15
0
Order By: Relevance
“…In contrast, Grüter and Rohde (2021) found that grammatical aspect did not modulate the prediction of upcoming reference in L2 speakers of English. The L2 speakers with varying L1s showed no difference between conditions in real-time processing, despite their native-like performance in an additional offline task.…”
Section: L1/l2 Differences In Cue Weightingmentioning
confidence: 67%
See 3 more Smart Citations
“…In contrast, Grüter and Rohde (2021) found that grammatical aspect did not modulate the prediction of upcoming reference in L2 speakers of English. The L2 speakers with varying L1s showed no difference between conditions in real-time processing, despite their native-like performance in an additional offline task.…”
Section: L1/l2 Differences In Cue Weightingmentioning
confidence: 67%
“…There, L2 speakers did not over-rely on a semantic cue as in the studies above, but they did not integrate a semantic and a grammatical cue, unlike an L1 group. In Grüter, Takeda, Rohde and Schafer (2018) and Grüter and Rohde (2021), participants had to integrate the lexical semantics of the verb and grammatical aspect to predict upcoming reference. For transfer-of-possession verbs such as in ( 5), more references to the goal argument were expected after completed events.…”
Section: L1/l2 Differences In Cue Weightingmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, there is evidence that not everyone can always engage in predictive processing [e.g., children, non-native speakers, and nonstudent and older adults (Huettig, 2015;Pickering and Gambi, 2018;Grüter et al, 2012)]. For example, nonnative speakers don't make the same coreference predictions that native speakers do in contexts with transfer-of-possession verbs, a finding that has been attributed to the increased difficulty of real-time nextmention computations during second language processing (Grüter and Rohde, 2021). Further research can thus shed light on whether our hypothesis regarding the differences witnessed in Experiments 1 and 3 is on the right track.…”
Section: Discussionmentioning
confidence: 99%